Location and contract pricing evaluation of distributed generation under a competitive framework - López-Lezama, J. M. (2011)
This paper presents a comparison between different approaches for the optimal location and contract pricing of dispatchable Distributed Generation (DG) in distribution systems. Regarding the ownership of DG, three different cases have been considered: a) when the DG units belong to the Distribution Company (DisCo); b) when the DG units belong to a single owner; and c) when the DG units belong to different owners. The location and contract pricing is evaluated considering a market structure in which the DisCo can purchase energy either from the DG units within its network, and/or from the wholesale energy market. Tests are performed using a 34-bus distribution system. The three cases are analyzed and compared.